Metabolism of bioactive compounds and antioxidant activity in bananas during ripening - de Souza, Angela Vacaro [UNESP]; de Mello, Jéssica Marques [UNESP]; da Silva Favaro, Vitória Ferreira [UNESP]; dos Santos, Tayla Gabrielly Ferreira; dos Santos, Gabriel Pereira; de Lucca Sartori, Diogo [UNESP]; Ferrari Putti, Fernando [UNESP] (Hindawi, 2021)
The study aimed to characterize bananas in their different stages of ripeness, to determine the variables that demonstrate higher levels at each moment. The fruits were analyzed according to physical parameters: weight, texture, and diameter of the fruits; as well as physicochemical parameters: pH, titratable acidity, soluble solids, and Ratio; and also biochemical parameters: total sugars, phenolic compounds, ascorbic acid, pigments, antioxidant activity by DPPH and FRAP methods. The used samples were collected at the following maturation stages: 2, 4, 6, and 7 and determined according to the Von Loesecke Maturation Scale. In relation to the behavior of the parameters evaluated, the fruits showed significant reductions in relation to the physical parameters, while there were increases in relation to pH, titratable acidity, and soluble solids. The antioxidant and phenolic activities also showed reductions, which shows that the degradative process caused by ripening also causes reductions in these compounds. Novelty impact statement: The main parameters and metabolites evaluated in the present study showed optimum values at the stages in which the consumption of fresh fruits is recommended. As the banana is a climacteric fruit, the obtained results showed interesting correlations, with emphasis on the physical parameters, which showed a reduction during ripening, and the physicochemical parameters, that increased, displaying a negative correlation between these groups. It becomes necessary to understand the physiology of the fruit, with emphasis, such as it has been done in this work, on the reactions of synthesis and degradation of primary and secondary metabolites in the ripening and senescence of the fruits, as well as their correlations between the evaluated parameters. Such study is necessary to have an understanding of the regulatory process and possible manipulation of the fruit, to increase service life and reduce losses.